Genome-Wide Identification and Expression Analysis of Eggplant Reveals the Key MYB Transcription Factor Involved in Anthocyanin Synthesis - Jiaqi Ai; Wuhong Wang; Tianhua Hu; Haijiao Hu; Yaqin Yan; Jinglei Wang; Yunzhu Wang; Na Hu; Hongtao Pang; Chonglai Bao; Qingzhen Wei (Horticulturae)
MYB transcription factors (TFs) represent one of the largest gene families in plants, and previous studies have demonstrated their involvement in regulating anthocyanin synthesis. Eggplant is an important anthocyanin-rich solanaceae vegetable crop. In this study, a total of 219 MYB gene-family members were identified using the complete and high-quality eggplant genome, comprising 105 1R-MYBs, 107 R2R3-MYBs, 5 3R-MYBs, and 2 4R-MYBs. Using phylogenetic analysis, we divided them into 33 subfamilies. Members of the SmeMYB gene family are unevenly distributed on 12 chromosomes, but are mainly concentrated at the upper and lower ends of the chromosomes. In addition, the expression levels of R2R3-MYBs in differently colored eggplant tissues (peel, calyx, stem, flower, and leaf) were investigated with RNA-seq (RNA sequencing). A total of 13 differentially expressed R2R3-MYB transcription factors related to the synthesis of anthocyanins in different eggplant tissues were screened out. SmeMYB110, SmeMYB175, and SmeMYB182 were also found to play significant roles in this process. Furthermore, 10 MYB TFs were identified as potential genes regulating anthocyanin synthesis in different tissues. The quantitative real-time PCR (qRT-PCR) analysis results showed that SmeMYB175 was regarded as the most likely key transcription factor regulating anthocyanin synthesis in calyx. These results not only deepen our understanding of the MYB gene family in eggplant but also lay a solid foundation for further research on the regulation of SmeR2R3-MYBs in anthocyanin synthesis across diverse eggplant tissues.